Democratic Crisis in the 21st Century and Research Challenges in Public Administration - Elisabete Santos,; Renata Alvarez Rossi, (Organizações & Sociedade, 2023)
Public administration research is constantly challenged to reflect on the complex relations between administration and democracy. The national and international reemergence of far right political forces, which use democratic ground rules as tools against classic liberal democracy, poses additional theoretical and epistemological challenges to the field. Which knowledge production challenges and perspectives appear in the field of administration, especially regarding the articulation between management models and democracy, considering society projects and development models? Such a debate requires mobilizing critical knowledge, redesigning study subjects, reframing participation, deepening the interdisciplinary character of research, and clarifying the political dimensions of the relationship between res publica and democracy